Pseudoclassical mechanics à la Faddeev-Jackiw - Caro, L. G. [UNESP]; De Gracia, G. B.; Pimentel, B. M. [UNESP]; Zambrano, G. E.R. (World Scientific Publishing, 2024)
In this study, we propose an extension of the formulation developed by Faddeev and Jackiw to include anticommutative variables in the language of supergeometry, as it could be a cost-effective way to determine the (Z2-graded) Poisson structure of theories describing spin-like degrees of freedom. Specifically, we apply the developed approach to pseudoclassical systems to lately use the standard canonical quantization program to check whether their already known quantum description is recovered.
Keywords: canonical quantization; Faddeev-Jackiw approach; Grassmann variables; pseudoclassical mechanics